A favorable path to domain separation in the orange carotenoid protein - Sharawy, Mahmoud (2022)
The orange carotenoid protein (OCP) is responsible for nonphotochemical quenching (NPQ) in cyanobacteria, a defense mechanism against potentially damaging effects of excess light conditions. This soluble two-domain protein undergoes profound conformational changes upon photoactivation, involving translocation of the ketocarotenoid inside the cavity followed by domain separation. Domain separation is a critical step in the photocycle of OCP because it exposes the N-terminal domain (NTD) to perform quenching of the phycobilisomes. Many details regarding the mechanism and energetics of OCP domain separation remain unknown. In this work, we apply metadynamics to elucidate the protein rearrangements that lead to the active, domain-separated, form of OCP. We find that translocation of the ketocarotenoid canthaxanthin has a profound effect on the energetic landscape and that domain separation only becomes favorable following translocation. We further explore, characterize, and validate the free energy surface (FES) using equilibrium simulations initiated from different states on the FES. Through pathway optimization methods, we characterize the most probable path to domain separation and reveal the barriers along that pathway. We find that the free energy barriers are relatively small (<5 kcal/mol), but the overall estimated kinetic rate is consistent with experimental measurements (>1 ms). Overall, our results provide detailed information on the requirement for canthaxanthin translocation to precede domain separation and an energetically feasible pathway to dissociation.